Geomorphological features drive spatiotemporal dynamics of young‐of‐the‐year brown trout populations in a large New Zealand river catchment. (1st April 2020) - Mikheev, Pavel B.; Jarvis, Matt G.; Matthaei, Christoph D.; Ingram, Travis; Nikiforov, Andrey I.; Closs, Gerard P.
Abstract: Determining the factors driving population dynamics of stream salmonids across broad landscapes is important for understanding stream ecosystem functioning and for the management and conservation of the populations of such fish. A few studies have described the determinants of the early life history of salmonids across catchments, but none of them have examined how this spatial variation develops temporally. We hypothesised that: (1) spatiotemporal dynamics of young‐of‐the‐year (YoY) trout populations vary within the catchment, with loss rates (emigration plus mortality) being higher in lower elevation, downstream reaches than in higher elevation, upstream ones; and (2) loss rate would be density dependent, leading to reduced intra‐ and inter‐cohort competition and supporting establishment of resident populations. We tested the first hypothesis by examining relationships between geomorphic characteristics of spawning streams and temporal dynamics of YoY brown trout density, loss rate and biological traits through an austral summer across the catchment of New Zealand's fourth‐longest river, the Taieri River. To test the second hypothesis, we examined whether initial YoY density in spring and other biotic determinants affected loss rate and cohort structure dynamics, resulting in density‐dependent self‐thinning of YoY fish to avoid resource limitation. Spring YoY density and subsequent loss rate was higher in low elevation sites, corresponding to stream accessibility to migratory spawners. These significant correlations of YoY density and related biotic variables with elevation disappeared later in the season, indicating that regardless of their origin, brown trout YoY tend to form stream resident populations with multicohort structure and densities low enough to limit intraspecific competition. Our findings provide evidence that geomorphological features of the landscape affect temporal dynamics of YoY trout populations driven by density‐dependent self‐regulatory mechanisms that can control the abundance of growing fish.